Creating Connections in the City: From road to street; and buffer zone to landscape: Residual highway space as a tool in stitching segregated neighbourhoods into the urban fabric - de Beer, Christine Caryl (School of Architecture, Planning and Geomatics, 2016)
Includes bibliographical references